The Effect of Green Human Resource Management on Business Sustainability Through Competitive Advantage in MSMEs in DKI Jakarta - KAMILIA, Alfina Ridha; NAWANGSARI, Lenny C (PT Keberlanjutan Strategis Indonesia, 2023)
Indonesia has environmental problems from year to year, which is still one of themain problems that must be faced. Awareness of the environment also triggers many companies to use environmentally friendly concepts as one of their company management policies. This study aims to examine and analyze The Effect Of Green Human Resource Management On Business Sustainability Through Competitive Advantage In MSMES In DKI Jakarta. The sample of this study was 212 respondents using an accidental sampling technique using the hair formula calculation due to the unknown population. The research method used is quantitative with SEM-PLS. The results show that: Green Recruitment has a significant effect on Business Sustainability; Green Training has a positive and significant effect on Business Sustainability; Green Performance Assessment has a positive and significant effect on Business Sustainability; Green Compensation and Rewards have no significant effect on Business Sustainability; Competitive Advantage has a significant effect on Business Sustainability; Green Recruitment has no significant effect on Competitive Advantage; Green Training has a positive and significant effect on Competitive Advantage; Green Performance Assessment has a positive and significant effect on Competitive Advantage; Green Compensation and Reward has a positive and significant effect on Competitive Advantage; Competitive Advantage does not mediate the effect of Green Recruitment on Business Sustainability; Mediating Competitive Advantage the effect of Green Training on Business Sustainability; Mediating Competitive Advantage effect of Green Performance Assessment on Business Sustainability; Mediating Competitive Advantage the effect of Green Compensation and Reward on Business Sustainability.